Living Hadith and Character Inculturation in Contemporary Preaching: A Case Study of Gus Iqdam’s Da’wah in Indonesia - Huda, Muhammad Khasanul; Mukoyimah (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
As a communication strategy in conveying religious messages, this study discusses character inculturation in Islamic da’wah in Indonesia with a focus on the use of regional languages, especially Javanese. This research uses Research methods, literature studies and case studies with a qualitative approach. This research also analyzes the implementation of character inculturation in da’wah through YouTube media, with a case study on Gus Iqdam’s da’wah through the channel “Mung Aran” This research aims to understand the concept of character inculturation in da’wah, evaluate the reality of cultural diversity in Indonesia, and analyze the implementation of Javanese language inculturation in Gus Iqdam's da’wah through YouTube media.This study finds that character inculturation in Islamic preaching, particularly through the use of Javanese language in digital platforms such as YouTube, is effective in creating emotional engagement with young audiences. Using Gus Iqdam as a case study, the research demonstrates how da'wah can bridge religious teachings with local cultural expressions, enabling prophetic values—especially those related to character—from hadith to be contextualized in everyday life. Overall, this research provides a transformative model for understanding Living Hadith in the digital age.This study offers a significant contribution to the field of Living Hadith studies by demonstrating how prophetic traditions are not only preserved but also dynamically embodied through digital preaching, particularly in the case of Gus Iqdam's da'wah on YouTube.